DETERMINING THE NUTRIENTS CHANGES AFTER UNDERGOING NUTRITIONAL COUNSELING AND COOKING ASSISTANCE AMONG T2DM OUTPATIENTS IN MALANG CITY, INDONESIA - Awalia Nanda Arianto; Rany Adelina; Sabrina Julietta Arisanty; Rafika Aprillia; Wisnowan Hendy Saputra; Risa Mafaza; Khairuddin Khairuddin; Tapriadi Tapriadi; Rathi Paramastri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: Nutrition and diets are critical factors for T2DM patients to maintain health. Nutrition education are considered less effective because most patients have not implemented them. This research tries to develop program innovation by combining nutrition counseling and cooking assistance for T2DM outpatients. This study aimed to know the risk factors for T2DM and determine the effectiveness of programmed nutrition education (NEP) on changes in nutrient intake in patients with T2DM. Methods: A total of 70 participants registered as T2DM outpatients at Kedung Kandang primary healthcare center in Malang city. Subjects were recruited using a 'quota sampling' technique. The design of this study is a quasi-experiment study using a comparison of the control (n=32)-treatment group (n=38). This research was conducted from September to November 2018. Fifty minutes of intensive individual counseling and cooking assistance were provided to T2DM patients and families. The data were analyzed using independent sample t-test, Wilcoxon Mann Whitney U-test, and logistic regression. The patients’ 4-d dietary records of 3 normal days and 1 holiday/weekend were assessed after 24 hours.Results: From this study it can be seen that intake of amino acid lysine was significantly higher in the treatment group than the control group (p = 0.04). The intake of fiber, MUFA, and PUFA was greater in the intervention group, while sodium intake was lower in the intervention group. The risk factors of T2DM incidence were age (p = 0.036), education (p = 0.043), waist circumference (p = 0.015), and carbohydrate intake (p = 0.033). Conclusion: T2DM patients treated with individual nutrition counseling and cooking assistance gained a higher intake of fiber, amino acid lysine, and unsaturated fatty acids. The most influential risk factors of T2DM incidence are age, education, waist circumference, and carbohydrate intake. Keywords: nutrition counseling, cooking assistance, nutritional intake, T2DM.